Principles of Place: Developing a Place-Based Ethic for Discussing, Debating, and Anticipating Technical Communication Concerns - Ross, Derek G.; Oppegaard, Brett; Willerton, Russell (IEEE transactions on professional communication, 2019)
Background: This paper offers a hybrid, place-based ethic drawn from multiple perspectives as a way to reinvigorate ethical thought for technical communicators. Literature review: Aldo Leopold's land ethic asks us to consider actions beyond our immediate surroundings. Martin Buber's dialogic ethics complement a land ethic and interrogate interpersonal communication. Anticipatory technology ethics recommends the integration of ethical discussions and decisions during the design phase of new technologies. Together, these three approaches inform a place-based ethic for technical communicators. Research questions: 1. How might we meaningfully merge the many ways that technical communicators from varying backgrounds approach ethics into a useful ethical model that considers human interaction, technological innovation, and physical place? 2. How might such a merged model, what we call a place-based ethic, affect technical communication design? Methods: We analyze cases including documents from radical environmental defense groups, a restyling of certain federal court rules from legalese into plainer language, the creation of mortgage documents suitable for consumers and industry professionals, and the action-research design phase of a locative mobile application about public art. Results and conclusion: The cases provide concrete examples of the components of a place-based ethic, and we conclude that designing with a place-based ethic includes actively acknowledging the value of the environment, seeking areas for dialogue among involved parties and celebrating dialogue where it occurs, seeking shared spaces, clearly stating anticipated outcomes, and usability testing for potential ethical issues.